2022
DOI: 10.3390/children9070931
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Patterns in Multisystem Inflammatory Syndrome in Children (MIS-C)-Characteristics and Prognostic Value

Abstract: Objective and design: Following COVID-19 infection, children can develop an hyperinflammatory state termed Multisystem Inflammatory Syndrome in Children (MIS-C). Lung Ultrasound (LUS) features of COVID-19 in children have been described, but data describing the LUS findings of MIS-C are limited. The aim of this retrospective observational study conducted between 1 March and 31 December 2020, at a tertiary pediatric hospital in Milano, is to describe LUS patterns in patients with MIS-C and to verify correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Achievements in pediatric practice include: Confirmation that LUS was able to detect peripheral lung consolidations in children, independent from disease severity [ 28 ]; The optimum correlation between LUS and CT findings, making LUS a safe option to assess children with COVID-19 and spare them from unnecessary radiation, at least in asymptomatic, mild and moderate disease [ 31 ]; Equal or better sensitivity than chest X-ray in detecting lung involvement during SARS-CoV-2 infection [ 32 ]; Usefulness in monitoring lung involvement during follow-up, shown in small studies and supported by previous experience from other viral pediatric respiratory infections [ 33 ]; Application in children with Multisystem Inflammatory Syndrome, one of the most severe post-infective complications of SARS-CoV-2 infection [ 34 , 35 ]. This finding is in agreement with previous pediatric studies that showed how lung ultrasound can detect cardiopulmonary interactions during acute systemic diseases [ 36 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Achievements in pediatric practice include: Confirmation that LUS was able to detect peripheral lung consolidations in children, independent from disease severity [ 28 ]; The optimum correlation between LUS and CT findings, making LUS a safe option to assess children with COVID-19 and spare them from unnecessary radiation, at least in asymptomatic, mild and moderate disease [ 31 ]; Equal or better sensitivity than chest X-ray in detecting lung involvement during SARS-CoV-2 infection [ 32 ]; Usefulness in monitoring lung involvement during follow-up, shown in small studies and supported by previous experience from other viral pediatric respiratory infections [ 33 ]; Application in children with Multisystem Inflammatory Syndrome, one of the most severe post-infective complications of SARS-CoV-2 infection [ 34 , 35 ]. This finding is in agreement with previous pediatric studies that showed how lung ultrasound can detect cardiopulmonary interactions during acute systemic diseases [ 36 ].…”
mentioning
confidence: 99%
“…LUS has also been successfully used in MIS-C. Specifically, a team from Rome described the first findings of vertical artifacts and simple pleural effusions, and a team from Northern Italy detected a cutoff of severity, predicting the need for intensive care admission, as well as inotropic or respiratory support [ 34 , 35 ]. Importantly, as MIS-C is a systemic condition, a wider application of point-of-care ultrasound that also assesses free abdominal fluids, the thickening of intestinal walls, and ventricular contraction would allow a better recognition and characterization of a child with suspected MIS-C, as described by two independent teams [ 37 , 38 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirms, on a larger populations, what initially suggested by smaller pediatric cohorts from Italy, Turkey and Spain, showing that children with LRTI during SARS-CoV-2 infection can have a cohort of LUS findings such as vertical artifacts and subpleural consolidations. [13][14][15][16][17][18][19][20][21][22] Authors from four different hospitals in Italy, in particular, found vertical artifacts and subpleural consolidations to be the most common findings, while pleural effusions were more rare and more described in children with MIS-C. However, cohorts were mostly limited to less than 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, while several adult studies on large cohorts have documented also a prognostic role of LUS in predicting hospitalizations and severe outcomes in infected adults, pediatric studies have provided less conclusive information, as they mostly included a small number of patients from single centers and without enough patients with moderate/severe disease. [9][10][11][12][13][14][15][16][17][18] For these reasons, we performed this multicenter national study in order to better characterize the clinical and prognostic role of LUS in children with Covid-19 assessed in the PED.…”
Section: Introductionmentioning
confidence: 99%